Description of thyroid disorders the year before conception: a population-based study - Tena Vivó, Glòria; Parellada Esquius, Neus; Cunillera Puértolas, Oriol; Albareda Riera, Mercè; Isidro Albaladejo, Mónica; Vila Ballester, Lluís (Frontiers in Endocrinology, 2023)
Objective This study aimed to monitoring the prevalence of previously identified thyroid disorders and hypothyroidism monitoring before pregnancy. Material and methods A retrospective cross-sectional study of women whose pregnancies occurred between 2014 and 2016 was conducted, including 120,763 pregnancies in Catalonia (Spain). The presence of thyroid disorders in women was based on disease diagnostic codes and/or prescription of levothyroxine or antithyroid drugs. To evaluate the thyroid disorder diagnosis and monitoring, thyrotropin (TSH), free T4 (FT4), antiperoxidase antibody (TPOAb), and anti-TSH receptor antibody (TRAb) records were gathered and categorised according to the reference values of each laboratory. Results The prevalence of recorded thyroid disorders before the last menstrual period was 5.09% for hypothyroidism and 0.64% for hyperthyroidism,showing a significant increase with age. A thyroid monitoring test was not performed in the year before the last menstrual period in approximately 40% of women with a known thyroid disorder. Amongst the women with hypothyroidism who underwent a TSH test, 31.75% showed an above-normal result. Amongst women previously unknown to have thyroid disorders, 3.12% had elevated TSH levels and 0.73% had low TSH levels. Conclusion A high percentage of Catalan women with a known thyroid disorder were not properly monitored during the year before pregnancy. Amongst those monitored, more than one-third had TSH values outside the reference range. Therefore, it is important to evaluate women with thyroid disorders during pre-pregnancy visits.